Effect of Dietary Fish Oil on Production Traits and Lipid Composition of Laying Hens - Al-Sultan, S.I. (International Journal of Poultry Science, 2005)
Feeding of fish oil at a concentration of 1.5 and 3% in a basal diet to laying hens for one month produced no significant effect on production traits except in the egg number and food conversion parameters. Fish oil had significantly reduced plasma total lipids, triglycerides, cholesterol and low and very low density lipoproteins. It`s suggested that fish oil may divert lipids metabolism to phospholipids formation, a mechanism explaining elevation in phospholipids observed in this study.